2018
DOI: 10.3390/ani8090150
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity and Interest in Working with Livestock Decreases the Odds of Having Positive Attitudes towards Non-Human Animals and Their Welfare among Veterinary Students in Italy

Abstract: Simple SummaryVeterinary students are the future generation of veterinary practitioners. Therefore, their attitudes towards non-human animals and animal welfare have a substantial impact on animal welfare itself. This study investigated the attitudes of veterinary students in Italy. The findings suggest that factors such as female gender, familiarity with pets, or the intention to work with pet species, as well as an animal-free diet, and membership in an animal rights association are the predictors of a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 47 publications
(71 reference statements)
2
29
0
Order By: Relevance
“…Lower attitudes towards animals and their welfare in veterinary students at higher study years were also recorded in other studies [6,[14][15][16]. In addition, previous studies showed veterinary students to express more positive attitudes and opinions towards CA welfare than towards farm animal welfare [17][18][19][20]. We wondered whether it also held true for Croatian veterinary students.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Lower attitudes towards animals and their welfare in veterinary students at higher study years were also recorded in other studies [6,[14][15][16]. In addition, previous studies showed veterinary students to express more positive attitudes and opinions towards CA welfare than towards farm animal welfare [17][18][19][20]. We wondered whether it also held true for Croatian veterinary students.…”
Section: Introductionsupporting
confidence: 51%
“…Similar results on owning CA by veterinary students have been reported by Magnani et al [19] as well. Another reason for veterinary students aspiring at having their career focused on CA could be that the study is predominated by female students who are mainly familiar with CA and strive to work with species other than farm animals [20]. The more so, considering the livestock reduction in Croatia [25], veterinary students can be expected to choose the CA segment of veterinary medicine, which has a stable foundation and is developing at a fast rate.…”
Section: Discussionmentioning
confidence: 99%
“…During the third step, consisting of the selection of the participants (P-set), we constructed a purposive sample [103,114] of 36 veterinary students who had completed the first three years of studies and were attending the first year of a master's degree in animal production. This was justified by their strong knowledge of animal welfare and their familiarity with the various facets of animal husbandry [115][116][117][118][119][120]. They have the potential to influence the meaning of animal welfare in the future by becoming stakeholders or being involved in policy processes.…”
Section: Methodsmentioning
confidence: 99%
“…These spaces and those existing between them (−3, −2, −1, +1, +2, +3) force the participants to classify the statements on AW according to the intensity of their disagreement, neutrality or agreement. We used a forced symmetric distribution [117] that obliges respondents to catalog the statements in the predefined grid [112].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation